A combined procedure for irreducible dislocation of patella in children with ligamentous laxity: A preliminary report - İnan, Muharrem; Sarıkaya, İlker Abdullah; Şeker, Ali; Beng, Kubilay (Turkish Assoc Orthopaedics Traumatology, 2015)
Objective: Irreducible patellar dislocation accompanying ligamentous laxity is rarely seen in pediatric patients. The most common complaints due to this condition are inability to walk, delayed walking, and difficulties with orthotics. The purpose of this retrospective study is to describe a novel surgical technique to treat dislocated patella in patients with symptomatic ligamentous laxity.Methods: Fourteen knees of 9 patients operated on by a single surgeon between 2009-2012 were included in the study. The tensor fascia was divided into 2 strips, and these strips were passed via the joint and sutured to themselves. The combined procedure additionally includes lateral capsular release, vastus lateralis (VL) resection, medial capsular plication, and Z-plasty of the rectus femoris (RF) tendon.Results: Mean age at the time of surgery was 6.9±3.3 years (range: 4-13 years). The mean follow-up was 37.6±0.9 months (range: 26-49 months). Patellofemoral instability was restored for all patients by using combined surgical technique. Patellar lateralization developed in 2 patients, in whom stability was obtained via secondary medial plication.Conclusion: Our results show that this combined surgical procedure stabilizes the knee and treats patellar dislocation accompanying ligamentous laxity in pediatric patients
Keywords: Irreducible; Ligamentous Laxity; Patellar Dislocation; Procedure